Implementation barriers and facilitators to a COVID-19 intervention in Bangladesh: The benefits of engaging the community for the delivery of the programme - Akter, Fahmida; Tamim, Malika; Saha, Avijit; Chowdhury, Imran Ahmed; Faruque, Omor; Talukder, Animesh; Chowdhury, Mohiuddin Ahsanul Kabir; Patwary, Monzur Morshed; Rahman, Albaab-Ur; Chowdhury, Morseda; Sarker, Malabika (BMC health services research, 2022)
BRAC (Bangladesh Rural Advancement Committee), the largest NGO globally, implemented a community-based comprehensive social behavior communication intervention to increase community resilience through prevention, protection, and care for COVID-19. We conducted implementation research to assess fidelity and explore the barriers and facilitators of this intervention implementation.
Gesehen am 29.06.2023